The Effect Of Service Quality And Customer Satisfaction On Customer Loyalty At Ario Workshop In Lahat Regency - Andre Oktiano Pratama; Mujari Mujari; Darwin Kesuma (Jurnal Fokus Manajemen, 2026)
This study aims to determine the effect of service quality and customer satisfaction on customer loyalty. Based on the results of multiple linear regression analysis, the regression equation obtained is Y = 18.358 + 0.267 X₁ + 0.252 X₂, indicating that if the variables of service quality and customer satisfaction are assumed to be zero, customer loyalty remains at a constant value of 18.358. The regression coefficient for service quality (X₁) is 0.267, meaning that an increase of one unit in service quality will increase customer loyalty by 0.267 units. Likewise, the regression coefficient for customer satisfaction (X₂) is 0.252, indicating that an increase of one unit in customer satisfaction will increase customer loyalty by 0.252 units. The t-test results show that service quality (t = 2.359; Sig = 0.022) and customer satisfaction (t = 2.008; Sig = 0.049) have a significant influence on customer loyalty since their significance values are less than 0.05. Furthermore, the F-test result shows an F value of 7.448 with a significance level of 0.001 < 0.05, which means that service quality and customer satisfaction simultaneously have a significant effect on customer loyalty. Based on these findings, it is recommended that the company continues to improve service quality and pay attention to customer satisfaction to maintain and enhance customer loyalty.